Patents information for humanities research: Could there be something? - Reymond, David (Iberoamerican Journal of Science Measurement and Communication, 2020)
Latour and co-authors proposed, in the Science and Technology Translation theory, to target the many SHS (Social and Human Science) questions addressed by social studies of sciences by considering, in complement to traditional academic matters, the complete social environment (political, economic or societal). Patents obviously are a potential primary information source to do so. We propose to extend this considering that recent changes have evolved in our capacity to do so. We propose three preliminary steps: (a) patent documents as providing a structured information source, (b) a patent database as a technical encyclopedia and (c) the recent expansion of the variety of uses and users in patent domains. We underline, furthermore, that minority research in the academic space does effectively use patent information, especially in SHS compared to other disciplines. We deliver an experiment to estimate the amount of data unconsidered by not questioning the huge database of the European Patent Office. By comparatively considering the terminology of the two branches of the Unesco thesaurus, namely the micro thesauri “Social and Human Sciences" and the “Information and Communication Science” branches, we evaluate a database response to the whole vocabulary. An in-depth analysis of one selected concept will complete the study. Results show that patent information may provide a quantity of documents for a wide range of academic research questions, from strategic to state of the art, and position advances aside from the Social Studies of Science. The free open source tool is also a way to practice digital humanities expected skills on real world corpora.